Genetic analysis of feet and legs in Nelore cattle - Vargas, Giovana [UNESP] (2015)
The aim of this study was to estimate variance components of two traits associated to feet and legs in Nelore cattle and identify putative genomic regions underlying the expression of these traits through genome-wide association (GWA) analyses. Feet and legs was evaluated by the assignment of visual scores at two different moments: FL1) binary trait measured at yearling (about 550 days of age), aimed to identify whether an animal had defects related to feet and legs (FL1=1) or not (FL1=0); FL2) feet and legs score ranging from 1 (less desirable) to 5 (more desirable) was assigned to the top 20% animals for the selection index adopted by the beef cattle breeding program PAINT (CRV Lagoa), which were measured around 2-5 months after the evaluation of yearling. The FL1 and FL2 traits were evaluated together with yearling weight (YW). The components of variance and covariance and breeding values were estimated by Bayesian inference, using two-trait animal models (three analyses: FL1-FL2, YW-FL1 and YW-FL2). The genome-wide association (GWA) analyses for FL1 and FL2 was performed using the weighted single-step GBLUP method, from which were estimated the SNP effects. Functional annotation was focused on the ten 1Mb windows explaining the largest fraction of the genetic variance for each trait. Posterior means (standard errors) of heritability estimates were equal to 0.18 (0.04) and 0.39 (0.07), for FL1 and FL2, respectively. The estimate of genetic correlation between FL1 and FL2 (-0.47) was of moderate magnitude and negative, as expected considering that the classification score that favors each trait represents numerical values assigned in opposite directions. The genetic correlation estimated between FL2 and YW (0.39) suggests that the average yearling weight of the studied population is currently not high enough to cause a negative association with feet and legs problems. The genetic trends estimated for FL1 and FL2 (-0.043 and ...